Immunotherapy-Related Imaging Findings in Patients with Gynecological Malignancies: What Radiologists Need to Know - Russo, Luca (Korean J Radiol, 2021)
Immunotherapy is an effective treatment option for gynecological malignancies. Radiologists dealing with gynecological patients undergoing treatment with immune checkpoint inhibitors should be aware of unconventional immune-related imaging features for the evaluation of tumor response and immune-related adverse events. In this paper, immune checkpoint inhibitors used for gynecological malignancies and their mechanisms of action are briefly presented. In the second part, patterns of pseudoprogression are illustrated, and different forms of immune-related adverse events are discussed.